Web technologies for commerce and services online - Khosrowpour 1951- (Advances in eletronic commerce, 2008)
"This book delivers a global perspective on the influence of electronic commerce on organizational behavior, development, and management in organizations, discussing issues such as information security; strategic management of electronic commerce; organizational learning; business process management; mediated enterprises; and electronic marketplaces. It will prove an essential addition to library collections worldwide"--Provided by publisher.